DC conductivity and threshold switching in iodine doped Ge-Se-Te glasses. Issue 23 (1st December 2021) - Hegazy, H.H.; Sati, Dinesh C.; Sharma, Pankaj; Jaafari, M.A.
Abstract: The composition and temperature-dependent dc conductivity of (Ge20 Se18 Te62 )100-x Ix (x = 0 and 8) glasses have been studied. The activation energy at constant current decreases, whereas with composition, it increases. The I – V characteristic curves for the glassy compositions show threshold switching. Iodine content shows a remarkable effect when introduced in Ge-Se-Te glasses on the switching properties. Variation in the threshold voltage ( V th ) with composition decreased from 334 to 308 V. The thickness and temperature dependency on V th is also examined. With increasing temperature, the V th decreases exponentially, whereas it increases as T 2 with an increase in the thickness of the glass samples. The thermal breakdown ΔT breakdown is also calculated. The threshold switching properties may be explored for numerous applications such as high-speed electronic memory and selector devices.